2019
DOI: 10.3390/molecules24091838
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Astragaloside IV against Cerebral Ischemia/Reperfusion Injury: Suppression of Apoptosis via Promotion of P62-LC3-Autophagy

Abstract: Background: Ischemia/reperfusion (I/R) caused by ischemic stroke treatments leads to brain injury, and autophagy plays a role in the pathology. Astragaloside IV is a potential neuroprotectant, but its underlying mechanism on cerebral I/R injury needs to be explored. The objective of this study is to investigate the neuroprotective mechanism of Astragaloside IV against cerebral I/R injury. Methods: Middle cerebral artery occlusion method (MCAO) and oxygen and glucose deprivation/reoxygenation (OGD/R) method wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 63 publications
(67 reference statements)
5
69
0
Order By: Relevance
“…In recent years, mounting evidence indicates that cerebral I/R injury closely relates to autophagy (Zhang et al, 2019a). The research by Zhang et al showed that astragaloside IV treatment exerted neuroprotective effects on cerebral I/R injury via the promotion of autophagy (Zhang et al, 2019b). LncRNA SNHG12-induced autophagy activation alleviated cerebral I/R injury, which was partially reversed by an autophagy inhibitor 3-MA (Yao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mounting evidence indicates that cerebral I/R injury closely relates to autophagy (Zhang et al, 2019a). The research by Zhang et al showed that astragaloside IV treatment exerted neuroprotective effects on cerebral I/R injury via the promotion of autophagy (Zhang et al, 2019b). LncRNA SNHG12-induced autophagy activation alleviated cerebral I/R injury, which was partially reversed by an autophagy inhibitor 3-MA (Yao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Astragaloside IV (As-IV), a primary bioactive compound of Radix Astragali, Astragalus mongholicus Bunge (Fabaceae), has been described as potential neuroprotective effect in experimental models of Alzheimer's disease and cerebral ischemia 22 . It has been found As-IV protected neurons from apoptosis and autophagy 23,24 , some by regulating Akt/GSK-3β/ β-catenin pathway [25][26][27] . As-IV could be a new therapeutic drug candidate for post-stroke treatment and effectively promote neural stem cells (NSCs) proliferation and neurogenesis in transient cerebral ischemic brains 28 .…”
Section: Introductionmentioning
confidence: 99%
“…It is soluble in highly polar organic solution [ 1 , 2 ]. Previous studies have shown protective effects of astragaloside IV on various organs such as heart [ 3 , 4 ], kidney [ 5 , 6 ], brain [ 7 , 8 ], and nerve [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%